Complex 3D-Printed Heat Transfer Surfaces: An Assessment and Comparison of Tools for Implicit Geometry Modelling - Martin Zálešák; Lubomír Klimeš; Pavel Charvát; Michal Spilácek (Chemical Engineering Transactions)
In the design of heat exchangers (HXs), an obvious effort is to maximise the heat transfer efficiency and performance while keeping the dimensions and costs of HXs as low as possible. Extended surfaces are a common technique for heat transfer enhancement, leading to an enlarged surface for the interaction of heat transfer fluids. Fins represent the most frequent extended surfaces used in the HX design. In the past, the shape of fins used in HXs was rather simple due to the limited capabilities of the available production technology. However, the rapid development of additive manufacturing (AM) and 3D printing has opened new possibilities in design and production. The AM allows for the production of HXs comprising heat transfer surfaces with a complex topology, which can possess a very high surface-to-volume ratio. In this respect, triply periodic minimal surfaces (TPMS) seem to be very promising. Gyroids and lidinoids are typical examples of such TPMS. Computer simulations are a common approach in the design of HXs. Simulations of HXs with such complex surfaces are, however, challenging. In the case of computational fluid dynamics (CFD) tools, the necessary input is the computational mesh, which is closely related to the domain geometry. The creation of the domain geometry adopting TMPS is rather demanding as TMPS are defined by implicit mathematical relationships and standard computer-aided design (CAD) modellers cannot be utilised for this purpose. The study presents an assessment and comparison of available computer tools for the implicit modelling and preparation of the TPMS-based geometry with implicit modelling. The results indicate that both commercial as well open-source tools exist for this purpose, enabling different levels of flexibility and user-friendliness.